(untitled) (Bangladesh Journal of Endosurgery, 2013)
Introduction: Rectal angiodysplasia is a rare lesion of bowel wall in pediatric population. Materials and Methods: We report the first laparoscopic management of a case of bifocal angiodysplasia in a child, involving the rectum and the left colonic flexure. The preoperative investigations showed only rectal lesions. A classic Swensons pull-through by laparoscopy was performed, with discovery of second lesion necessitating a resection of the left colonic flexure. Result: At day 11, the child presented an occlusive syndrome and a partial disunion of the coloanal anastomosis, requiring a discharge transverse colostomy Two months after closure of the colostomy, the child regained 1 kg, had a normal transit (3 to 4 defecations per day) and normal haemoglobin results. DOI: http://dx.doi.org/10.11593/bje.2013.0101.0001 Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 13-15